Liver microbial community and associated host transcriptome in calves with feed induced acidosis - Li, Wenli; Larsen, Anna; Murphy, Brianna; Fregulia, Priscila (Frontiers in Veterinary Science, 2023)
In the dairy industry, calves are typically fed diets rich in highly fermentable carbohydrates and low in fibrous feeds to maximize ruminal papillae and tissue development. Calves on such diets are vulnerable at developing ruminal acidosis. Prevalent in cattle, liver abscess (LA) is considered a sequela to ruminal acidosis. LAs can cause significant liver function condemnation and decreased growth and production. Currently, we know little about the liver microbiome in calves with feed-induced acidosis. Using our established model of ruminal acidosis, where young calves were fed an acidosis-inducing (AC) or -blunting (control) diet starting at birth until 17-week of age, we investigated microbial community changes in the liver resultant from ruminal acidosis. Eight calves were randomly assigned to each diet, with four animals per treatment. Rumen epithelium and liver tissues were collected at 17 weeks of age right after euthanasia. Total RNAs were extracted and followed by whole transcriptome sequencing. Microbial RNA reads were enriched bioinformatically and used for microbial taxonomy classification using Kraken2. AC Calves showed significantly less weight gain over the course of the experiment, in addition to significantly lower ruminal pH, and rumen degradation comparison to the control group (P < 0.05). In the liver, a total of 29 genera showed a significant (P < 0.05) abundance change ( > 2-fold) between the treatments at 17-week of age. Among these, Fibrobacter, Treponema, Lactobacillus, and Olsenella have been reported in abscessed liver in cattle. Concurrent abundance changes in 9 of the genera were observed in both the liver and rumen tissues collected at 17-week of age, indicating potential crosstalk between the liver and rumen epithelial microbial communities. Significant association was identified between host liver gene and its embedded microbial taxa. Aside from identifying previously reported microbial taxa in cattle abscessed liver, new repertoire of actively transcribed microbial taxa was identified in this study. Our work sheds light into host liver community changes associated with acidosis in post-weaning calves. Further investigation is needed to study liver microbiome colonization and assembly resultant from ruminal acidosis, and specific molecular events that facilitate the interactions between the gut and the liver.